2018
DOI: 10.1007/s12035-017-0859-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Peroxynitrite-Induced Mitophagy Activation Attenuates Cerebral Ischemia-Reperfusion Injury

Abstract: Activated autophagy/mitophagy has been intensively observed in ischemic brain, but its roles remain controversial. Peroxynitrite (ONOO), as a representative of reactive nitrogen species, is considered as a critical neurotoxic factor in mediating cerebral ischemia-reperfusion (I/R) injury, but its roles in autophagy/mitophagy activation remain unclear. Herein, we hypothesized that ONOO could induce PINK1/Parkin-mediated mitophagy activation via triggering dynamin-related protein 1 (Drp1) recruitment to damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 58 publications
1
58
0
Order By: Relevance
“…All these studies revealed that autophagy plays neuroprotective roles after cerebral I/R injury. Reports also demonstrate that autophagy is deleterious for ischemic brain (Zhou et al, 2017;Feng et al, 2018). This discrepancy might be caused by different animal strains, ischemic models, and time of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies revealed that autophagy plays neuroprotective roles after cerebral I/R injury. Reports also demonstrate that autophagy is deleterious for ischemic brain (Zhou et al, 2017;Feng et al, 2018). This discrepancy might be caused by different animal strains, ischemic models, and time of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Since systemic KOs of non-redundant Atg genes are lethal (Kuma et al, 2017), and even tissue-specific KOs lead to pathology (e.g. Koike et al, 2008), in order to show the necessity of autophagy for cell loss, researchers have resorted to non-specific drugs such as the phosphatidylinositol 3-kinase (PI3K) inhibitor 3-MA (Wen et al, 2008;Puyal et al, 2009;Feng et al, 2018), or less efficient lentiviral-based shRNAmediated knockdowns (Matsui et al, 2007;Zheng et al, 2009;Ginet et al, 2014). Furthermore, the read-out is overall loss of viable tissue (i.e.…”
Section: Adcd In Pathophysiological Conditionsmentioning
confidence: 99%
“…Another recent study has provided evidence for mitophagy in infarcted tissue from adult rats following cerebral ischemia-reperfusion injury. Notably, infarct size was reduced by administration of either the non-specific autophagy inhibitor 3-MA, or a specific inhibitor of Drp1, a factor that is necessary for mitochondrial fission and the recruitment of the mitophagy regulators PINK1 and Parkin to the mitochondria (Feng et al, 2018). Of note, as it is much more difficult to demonstrate mitophagy in vivo, and, furthermore, to prove that it specifically causes cell death, there are not many unambiguous examples in the literature of lethal mitophagy in pathophysiological scenarios.…”
Section: Death From Over-eatingelimination Of Intracellular Organellementioning
confidence: 99%
“…Tunicamycin and thapsigargin-induced ER stress protects against ischemic stroke injury, which is probably involved in mitophagy induction [178]. Peroxynitrite-induced PINK1/Parkin-mediated mitophagy activation through drp1 recruitment to damaged mitochondria aggravates cerebral I/R injury during stroke [179]. A natural antioxidant naringin potentially inhibits peroxynitritemediated mitophagy activation by inhibiting the translocation of Parkin to the mitochondria and attenuating ischemic stroke injury [180].…”
Section: Clinical Drugs and Chemical Reagentsmentioning
confidence: 99%